Asenkron Makinanın Kontrolünde Optimum Pı Tasarımı Ve Bulanık-pı İle Karşılaştırılması - Özkan, Devrim (Fen Bilimleri Enstitüsü, 2015)
Bu çalışmada asenkron makinanın kontrolü için kullanılan PI kontrolörlerin, kontrolör katsayılarının bulunması için bir sayısal optimizasyon yöntemi kullanılmış ve makinanın değişik çalışma koşulları için elde edilen sonuçlar gözlemlenmiştir. Çalışmanın ikinici aşamasını bulanık kontrolörler oluşturmaktadır. Bilindiği üzere bulanık kontrol geride bıraktığımız on yıl içerisinde giderek daha sık kullanılan, anlaşılması ve uygulanması oldukça kolay bir yöntem olarak kontrol ve otomasyon alanındaki yerini sağlamlaştırmıştır. Çalışmanın son aşamasında asenkron makinada kullanılan PI kontrolörlerden birinin yerine bir bulanık-PI kontrolör yerleştirilmiş ve bu koşullarda elde edilen sonuçlar gözlemlenmiştir.

Recently, excitation systems which need variable speed and flux parameters are often used in induction motor systems. To control such systems we can use vector control units. Direct vector control is a part of vector control in which, parameters like speed, torque, flux, etc. are generally controlled using PI controllers. In this work, a numerical optimization method is used to find appropriate PI controller constants and the results are observed for different operating conditions of the machine. Fuzzy controllers constitute the second part of this work. The fuzzy logic has been a very popular control method since the beginning of 1990s. This popularity comes from the simplicity in the comprehension and application of the method. In the last part of the work, one of the PI controllers is replaced by a Fuzzy-PI controller and the results obtained under the given conditions are observed.
Optimal Pi Design In The Control Of Induction Machine And Comparison With Fuzzy-pi
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2003
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2003
Keywords: Asenkron Makina; Vektörel Kontrol; PI Kontrolör; Bulanık Kontrol; Induction Machine; PI Controller; Vector Control; Fuzzy Control